A Contingency Approach to Proactiveness - Business Performance Relationship - Bedi, Harpreet Singh (Indian Journal of Marketing, 2018)
The proactiveness - business performance relationship was examined in this study by adopting a descriptive and cross-sectional research design. Structural equation modeling was applied on a purposive sample of 457 North Indian firms to assess the impact of proactiveness on business performance. Moderating effect of environmental turbulence on proactiveness – business performance relationship was also assessed. The study found proactiveness as a significant predictor of business performance. The study revealed that firms operating in a dynamic environment were likely to be benefitted more from the pursuit of proactiveness. The findings provoke managers and entrepreneurs to adopt forward-looking and opportunity-seeking perspectives to achieve robust business performance. Managers of Indian firms can draw insights from this study and can better decide the strategic posture of their firms.